2019
DOI: 10.1111/eip.12892
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners' management of young people with mental health conditions in Australia

Abstract: Aim: Detecting and diagnosing youth mental health issues can be challenging for General Practitioners (GPs) who are often the first to encounter them. One aim of this study was to understand the challenges GPs faced in identifying, treating and referring young people with mental health issues in Melbourne, Australia. A second aim was to identify gaps in GP knowledge and service provision in order to design a service and training program for GPs that addresses those gaps.Method: A representative sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The child-predominant GPs may also have had more positive attitudes toward caring for children and families and communicated this positivity to parents. Studies of GPs with special interests have found that their attitudes and confidence are, understandably, shaped by their prior experiences . Conversely, we found that the trained adult-predominant GPs’ patients improved the least.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The child-predominant GPs may also have had more positive attitudes toward caring for children and families and communicated this positivity to parents. Studies of GPs with special interests have found that their attitudes and confidence are, understandably, shaped by their prior experiences . Conversely, we found that the trained adult-predominant GPs’ patients improved the least.…”
Section: Discussionmentioning
confidence: 47%
“…Studies of GPs with special interests have found that their attitudes and confidence are, understandably, shaped by their prior experiences. Conversely, we found that the trained adult-predominant GPs’ patients improved the least. It may be that these GPs relative lack of experience with child and youth problems could have led to treatment attempts that were off-putting to parents and children.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 LIT REVIEW HPs working with young people should engage in ongoing professional development with support from experienced clinicians. 8,[12][13][14][15] Continuity of care and youth mental health services Continuity of Care: Effective evidence-based models of continuity of care in mental health services include brief interventions, medication, patient self-management, specialist treatment, and/or inclusion of shared treatment plans with clinical and non-clinical services. 5,16 Coordination of local services in regional, rural, and remote areas may lead to more effective care and better health outcomes for youth, compared with service providers working independently.…”
Section: Background/issues Associated With Youth Mental Health Servicesmentioning
confidence: 99%
“…As noted previously, they prefer to the same GP or group of clinicians over time. 9,13,30,32 It is important to note that GPs who consult frequently with youth with mental health issues have higher levels of confidence in identifying and treating mental health issues. 13 Accessing preferred services and practitioners may be difficult for youth who live outside main population centres, however, the advent of telehealth services has improved service use, particularly for specialist services such as telepsychiatry.…”
Section: Service Use and Youth Mental Health Servicesmentioning
confidence: 99%
“…There is additionally a need to consider how assessment intention may vary for different professional groups. Although clinicians within specialist psychosis services reportedly lack self-efficacy in, and have concerns regarding, discussing voice-hearing experiences with young patients ( Bogen-Johnston et al, 2020 ), primary care clinicians report lack of confidence in interviewing ( Brunero et al, 2018 ) and anxiety in supporting people with mental health difficulties more generally ( Roberts et al, 2013 ), and the least confidence in identifying and managing psychotic experiences, such as voice-hearing, in youth, compared to other mental health problems ( Kehoe et al, 2020 ). Moreover, medical professionals have been found to hold more stigmatizing attitudes toward people with psychosis compared to mental health professionals ( Hori et al, 2011 ; Mittal et al, 2014 ; Smith et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%